Effect of gold nanoparticles and electrode drying time on reduced graphene oxide–based composite with respect to peak current of cyclic voltammetry - Abdul Guthoos, Habibah Farhana; Noorin, Nik Nurfaten; Ismail, Nur Alya Batrisya; Tumian, Afidalina; Wan Salim, Wan Wardatul Amani (Asian Research Publishing Network (ARPN), 2018)
Screen-printed glassy carbon electrodes (GCEs) 2 mm in diameter deposited with composites of reduced graphene oxide-gold nanoparticles (rGO-AuNPs), reduced graphene oxide–cellulose (rGO-cellulose), and reduced graphene oxide– gold nanoparticles-cellulose (rGO-AuNPs-cellulose) were characterized in terms of the effect of drying time on the peak oxidative current and surface roughness. From the cyclic voltammetry (CV) graph, at 12 hrs of electrode drying time in ambient airtherGO-AuNPs/GCE showed the highest anodic peak current of 1252.82 µA, in comparison to therGOcellulose/GCE with the lowest at 24.64 µA. FESEM results show that the rGO-AuNPs composite has the roughest surface morphology as well. Furthermore, there seem to be two layers of surface morphology in cellulose-based samples. The results obtained suggest that rGO-AuNPs/GCEs with 12 hours drying time have the highest peak current and the largest surface area owing to its roughness, thus implying that rGO-AuNPs has the most electrode area involved in redox reactions. The results also suggest the rGO-AuNPs nanocomposite can be effective as a sensitive transducer material for an electrochemical biosensor.